Analisis Problematika Belajar Siswa Kelas III pada Proses Pembelajaran di Sekolah Dasar - Marsela Puspita Br Damanik; Khairunnisa Khairunnisa (Jurnal Merah Putih Sekolah Dasar, 2026)
Learning in elementary school is an important process in forming students' knowledge, attitudes and skills. However, in its implementation, various learning problems were still found experienced by students in the classroom, especially in class III elementary school students. This research aims to analyze various student learning problems in the classroom, factors that influence the emergence of learning problems, as well as efforts that teachers can make to overcome learning obstacles so that the teaching and learning process can take place effectively and conducively. This research uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews and documentation involving third grade teachers and elementary school students as research subjects. The results of the research show that students' learning problems in the classroom include lack of concentration during learning, low motivation to learn, difficulty understanding lesson material, less active in the learning process, often talking to friends when the teacher explains the material, and students' low self-confidence in expressing opinions or answering teacher questions. These problems are influenced by internal and external factors. Internal factors include low interest in learning, students' emotional condition, ability to understand different material, and lack of readiness to learn. Meanwhile, external factors include learning methods that are less varied, use of learning media that is not optimal, classroom environmental conditions that are less conducive, and lack of attention and support from the family environment. Efforts made by teachers to overcome student learning problems include using more interesting and interactive learning methods, providing learning motivation to students, creating a pleasant classroom atmosphere, using learning media that suit the characteristics of elementary school students, and paying special attention to students who experience learning difficulties. With these efforts, it is hoped that student learning problems can be minimized so that learning outcomes and student activity in learning can increase optimally.